Does Discipline Matter? Issues in the Design and Implementation of Management Development Programmes for Heads of Academic Departments - HUNTLEY-MOORE, SYLVIA (My University, 2003)
Government enquiries, universities and academic developers have all pointed to the need for systematic management development programmes for heads of academic departments. After noting that there were few examples of successful programmes in the literature and having met with limited success with one of their own, the authors conducted a needs analysis which included a survey of heads and o ther stakeholders. Analysis of the survey results indicates the existence of perceptual differences between academics from differing discipline cultures as to the importance of a range of possible heads? roles and of the need for professional development i n them. This finding suggests that management development programmes should take more account of such cultures than appears to have been the case to date. Reasons for the differences should be the subject of further research
PUBLISHED
Keywords: Education